Relational‐Cultural Theory and Reality Therapy: A Culturally Responsive Integrative Framework. (January 2017) - Haskins, Natoya Hill; Appling, Brandee
Abstract : The authors propose an integration of relational‐cultural theory and reality therapy. The authors contend that the traditional assumptions of reality therapy are consistent with the relational aspects of relational‐cultural theory and together provide a culturally responsive approach for diverse clients. The authors also include an overview of the 2 theories as well as highlight the convergences and divergences. In addition, the authors present a case illustration depicting the integration method in practice.